THE CAUSES AND CONSEQUENCES OF FAMILY VIOLENCE AGAINST CHILDREN IN DEBRE MARKOS TOWN, ETHIOPIA - Mekuriyaw, Edemealem (PEOPLE: International Journal of Social Sciences, 2017)
The focus of this paper was to assess the causes and consequences of family violence against children in Debre Markos town. The paper employed qualitative research approach. It employed case study research design. It used both secondary and primary sources of data. The data were gathered from secondary sources such books, journal articles, and report papers through document analysis. In addition, it employed unstructured interview to collect primary data from key informants. The key informants were selected through purposive sampling. There was an intensive family violence in Debre Markos town. There were various causes of family violence in Debre Town. The major causes of family violence in Debre Markos town were the weak enforcement of policies, backward traditions, poor socio-economic status, and dysfunctional family relationship. Family violence had many negative effects on children. Children faced cognitive and biological, social and economic, psychological, and physical problems due to family violence in Debre Markos town.